Defining the Effect of Teachers' Medical History on their Inclusive Teaching Practice: Analyzing Feelings of Competence and Knowledge in Inclusive Physical Education - Omar Ben Rakaa; Mustapha Bassiri; Said Lotfi (OVS LLC, 2024)
Background. The process of including special students in the school system has prompted a comprehensive examination of strategies to ensure equity in school justice, the quality of learning, and the harmonious development of students' potential. The efficacy of these strategies is contingent upon the life experiences and medical backgrounds of the educators in question. Objectives. The study aimed to evaluate the extent to which personal and family medical histories impact teachers' sense of pedagogical competence (TSPC) and their knowledge (TK) of students' physical activity management. Materials and Methods. The methodology entailed the distribution of an online questionnaire to 339 physical education and sports (PE) teachers, comprising 159 females and 180 males over the age of 21, employed in public schools at the high school and middle school levels. The measurement instrument consisted of four sections: socio-demographic characteristics, personal and family background, sense of pedagogical competence, and teacher knowledge. Results. The findings indicate a notable prevalence of diseases such as obesity and diabetes in males compared to females, with a significant predominance in older people. It is demonstrated that gender has a particular influence on TSPC and TK in managing hypertensive students. Furthermore, older teachers and those employed in urban settings tend to exhibit greater self-efficacy, despite the absence of a statistically significant association between their initial PES training and TSPC and knowledge outcomes. There is a positive correlation between TSPC and teacher knowledge. Conclusions. To sum it up, older teachers are more susceptible to developing illnesses such as diabetes, hypertension, and obesity. This medical history has a significant impact on the development of inclusive skills and knowledge of school-related pathologies.